Network Formation of Catanionic Vesicles and Oppositely Charged Polyelectrolytes. Effect of Polymer Charge Density and Hydrophobic Modification - Antunes, Filipe E. (2004)
In nonequimolar solutions of a cationic and an anionic surfactant, vesicles bearing a net charge can be spontaneously formed and apparently exist as thermodynamically stable aggregates. These vesicles can associate strongly with polymers in solution by means of hydrophobic and/or electrostatic interactions. In the current work, we have investigated the rheological and microstructural properties of mixtures of cationic polyelectrolytes and net anionic sodium dodecyl sulfate/didodecyldimethylammonium bromide vesicles. The polyelectrolytes consist of two cationic cellulose derivatives with different charge densities; the lowest charge density polymer contains also hydrophobic grafts, with the number of charges equal to the number of grafts. For both systems, polymer−vesicle association leads to a major increase in viscosity and to gel-like behavior, but the viscosity effects are more pronounced for the less charged, hydrophobically modified polymer. Evaluation of the frequency dependence of the storage and loss moduli for the two systems shows further differences in behavior: while the more long-lived cross-links occur for the more highly charged hydrophilic polymer, the number of cross-links is higher for the hydrophobically modified polymer. Microstructure studies by cryogenic transmission electron microscopy indicate that the two polymers affect the vesicle stability in different ways. With the hydrophobically modified polymer, the aggregates remain largely in the form of globular vesicles and faceted vesicles (polygon-shaped vesicles with largely planar regions). For the hydrophilic polycation, on the other hand, the surfactant aggregate structure is more extensively modified: first, the vesicles change from a globular to a faceted shape; second, there is opening of the bilayers leading to holey vesicles and ultimately to considerable vesicle disruption leading to planar bilayer, disklike aggregates. The faceted shape is tentatively attributed to a crystallization of the surfactant film in the vesicles. It is inferred that a hydrophobically modified polyion with relatively low charge density can better stabilize vesicles due to formation of molecularly mixed aggregates, while a hydrophilic polyion with relatively high charge density associates so strongly to the surfactant films, due to strong electrostatic interactions, that the vesicles are more perturbed and even disrupted.